2022
DOI: 10.1021/acs.macromol.1c02283
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Supramolecular Nucleating Agents for Poly(3-hexylthiophene)

Abstract: Controlling the solid-state morphology of semiconducting polymers is crucial for the function and performance of optoelectronic and photonic devices. Nucleation is a commonly used and straightforward approach to tailor the solid-state morphology of semi-crystalline polymers. However, efficient nucleating agents for semiconducting polymers are still rare. Here, we present a conceptual approach to tailor supramolecular nucleating agents for the semiconducting polymer, poly(3-hexylthiophene) (P3HT). Using this ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…[ 60–62 ] Nucleating agents can promote the microstructure formation, i.e., crystallization, of conjugated polymers during the film forming process and the thermal annealing process. [ 60,63,64 ] Additional GIXD results for non‐annealed DPPDTT/1‐NIPS films provide the evidence that 1‐NIPS promotes the crystallization of DPPDTT during thermal annealing process (Figure S29, Supporting Information). For RR‐P3HT films, added 1‐NIPS molecules were also located at amorphous regions and changed the crystalline ordering depending on the added amount of 1‐NIPS (Figure S30 and Table S4, Supporting Information).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…[ 60–62 ] Nucleating agents can promote the microstructure formation, i.e., crystallization, of conjugated polymers during the film forming process and the thermal annealing process. [ 60,63,64 ] Additional GIXD results for non‐annealed DPPDTT/1‐NIPS films provide the evidence that 1‐NIPS promotes the crystallization of DPPDTT during thermal annealing process (Figure S29, Supporting Information). For RR‐P3HT films, added 1‐NIPS molecules were also located at amorphous regions and changed the crystalline ordering depending on the added amount of 1‐NIPS (Figure S30 and Table S4, Supporting Information).…”
Section: Resultsmentioning
confidence: 96%
“…2D‐GIXD was measured with a critical angle of each sample (beam intensity 11.06 keV) at Pohang Accelerator Laboratory beamlines 3C and 9A. [ 64 ] DMTA was conducted using TA Instruments Q850 with a film tensile kit. Samples were prepared by drop‐casting high‐concentration (20 mg·mL −1 ) polymer solutions in chloroform to achieve suitable evaporation on both sides of the glass fiber mesh on an N 2 environment hot plate (≈ 50 °C) and dried in a vacuum oven overnight at the same temperature to drive off residual water molecules and solvents.…”
Section: Methodsmentioning
confidence: 99%
“…Heterogeneous nucleating agents (NAs) are known to provide an epitaxial surface from which the polymer crystallization is initiated, and subsequently, crystal growth proceeds in a defined manner. , Achieving very densely packed and oriented nanofibers of P3HT requires NAs with a highly regular surface and a large number of nucleation sites. In our recent work, we have shown that a supramolecular NA based on N , N ′-1,4-phenylenebis­[4-pyridinecarboxamide] (compound 1 , see Scheme ) is an excellent nucleating agent for the oriented crystallization of P3HT …”
Section: Resultsmentioning
confidence: 99%
“… a The molecular design combines the ability to form stable supramolecular aggregates via hydrogen bonding of the amide linkages, resulting in epitaxial surfaces with the ability to form attractive pyridine–thiophene interactions to nucleate P3HT …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation